If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + -38 = -3x + 7 Reorder the terms: -38 + -6x = -3x + 7 Reorder the terms: -38 + -6x = 7 + -3x Solving -38 + -6x = 7 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -38 + -6x + 3x = 7 + -3x + 3x Combine like terms: -6x + 3x = -3x -38 + -3x = 7 + -3x + 3x Combine like terms: -3x + 3x = 0 -38 + -3x = 7 + 0 -38 + -3x = 7 Add '38' to each side of the equation. -38 + 38 + -3x = 7 + 38 Combine like terms: -38 + 38 = 0 0 + -3x = 7 + 38 -3x = 7 + 38 Combine like terms: 7 + 38 = 45 -3x = 45 Divide each side by '-3'. x = -15 Simplifying x = -15
| 4(2x+3)+6=4x+14 | | 4n^2+4n-17=0 | | 4e-3=-3 | | 7(-6-4x)=154 | | 2(2x+1)+7=-4x-47 | | 6.52=5y | | 3x^2y^3-12x^2y+6xy=0 | | 4(-2-2x)=-96 | | 7w=22.4 | | 14y=3x+7 | | 3(5-2x)=-39 | | 6i*x= | | 46=3(4x-5)+1 | | -5(1x+1)=50 | | 4x=7y+14 | | x^2=ROT-1 | | -3(4h-k)+(5h-2k)= | | 6v+6-2(-4v-2)=5(v-1) | | -7(2+4x)=294 | | 0.10x+0.30x=2.5 | | 9y=-7x+6 | | r^2=-5r-4 | | 8m+6m-12=72 | | -5(9-x)=-10 | | 5(2x-3)=-35 | | 5x+2(x+8)=37 | | -5(-6+7x)=390 | | y=0.5*9-10 | | 3(95+6x)=x+152 | | 4z+9=2z+9 | | 12j=1(j-8) | | 7(5-7x)=-455 |